STUDI KELAYAKAN USAHA AGROINDUSTRI TEMPE MOSACCHA DI KOTA BANDAR LAMPUNG - Rizal, Samsul; Melatiningsih, Atri; Hidayati, Sri; Kustyawati, Maria Erna; Endaryanto, Teguh (BPFP Faperta UNIB, 2023)
Mosaccha tempeh is a type of tempeh made using an inoculum containing Rhizopus oligosporus inoculum with the addition of Saccharomyces cerevisiae. The addition of Mosaccha tempeh inoculum produces tempeh that is more delicious to eat, more durable, and is expected to have better health benefits because it contains beta-glucan. Analysis of the feasibility of the Mosaccha tempe agorindustrial business needs to be carried out to find out whether the establishment of the business is feasible or not feasible to run. This study aims to determine the feasibility of establishing Mosaccha tempeh agro-industry in Bandar Lampung City based on financial aspects. The research method used is descriptive analysis to describe the design of the Mosaccha tempe industry through the stages of the observation and analysis process of data from observations and interviews. The methods used were observation and interviews. The data used in this research is primary data which is further analyzed using Microsoft Excel and secondary data as a reference in marketing aspects. The financial analysis used is NPV, Net B/C, IRR, and PP analysis. The research results show that the Mosaccha tempeh agro-industry business has a Net Present Value of IDR 2.450.599.432,50 (> 0), an Internal Rate Return value of 76% (> 12%), a Net B/C value of 1.49 (> 1), while the value of Payback Period is 1.67 years, faster than the age of the project. Based on these results, the production of Mosaccha tempeh with a capacity of 200 kg of soybean raw material/day is feasible to be developed in Bandar Lampung City.